2001
DOI: 10.1111/1467-8624.00296
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Pathways from Child Maltreatment to Peer Rejection

Abstract: Using a prospective longitudinal design, rejection by peers, aggressive behavior, and social withdrawal were examined among a representative community sample of 107 maltreated children and an equal number of non-maltreated children. Results revealed that chronic maltreatment was associated with heightened risk of rejection by peers. Chronically maltreated children were more likely to be rejected by peers repeatedly across multiple years from childhood to early adolescence. Maltreatment chronicity was also asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
212
2
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 314 publications
(238 citation statements)
references
References 98 publications
17
212
2
7
Order By: Relevance
“…Adequate reliability has been obtained (weighted κs = .86-.98; Manly et al, 2001). Other investigators have demonstrated that the MCS is reliable and valid in classifying maltreatment (Bolger & Patterson, 2001;Bolger et al, 1998;English et al, 2005;Manly et al, 1994Manly et al, , 2001Smith & Thornberry, 1995;Stouthamer-Loeber, Loeber, Homish, & Wei, 2001). …”
Section: Maltreatment Classification System (Mcs)mentioning
confidence: 98%
“…Adequate reliability has been obtained (weighted κs = .86-.98; Manly et al, 2001). Other investigators have demonstrated that the MCS is reliable and valid in classifying maltreatment (Bolger & Patterson, 2001;Bolger et al, 1998;English et al, 2005;Manly et al, 1994Manly et al, , 2001Smith & Thornberry, 1995;Stouthamer-Loeber, Loeber, Homish, & Wei, 2001). …”
Section: Maltreatment Classification System (Mcs)mentioning
confidence: 98%
“…3. Combination of these measures may raise some concern that different forms of abuse are being confounded, but factor analyses of different types of child abuse by Bolger and Patterson (2001) found that physical and emotional abuse load on the same factor. Brezina (1998) also found similar results in a factor analysis of measures of physical and emotional maltreatment experienced in adolescence.…”
Section: Notesmentioning
confidence: 99%
“…Specifically, two mothers gave accounts of experiencing symptoms of depression and epilepsy, which are symptoms of psychological disorders. These results seem to support that unjustified parenting behaviors such as physical child abuse have the most damaging influences (Bolgar & Patterson, 2001) and, at the same time, have consequences in the child showing symptoms of stress-related psychological disorders (Briere, 1992). As have stated, such unjust rearing experiences may lead the internal working model of insecurely attached participants formed during infancy to a more preoccupied manner that continues throughout their adulthood.…”
Section: Discussionmentioning
confidence: 59%